Assessing policies for attracting international students: case of Malaysia - Tham,, Siew Yean; Nik Mahmod, Nik Ahmad Kamal; Alavi, Rokiah (Routledge, 2013)
While the world market for international students in higher education is dominated by traditional major players such as the US, UK and Australia, Malaysia has emerged as a recent contender with a market share of 2%. There is a gap in the literature in assessing the contributions of policy initiatives, including trade agreements, towards attracting inbound international students, especially from emerging contenders such as Malaysia. The objective of this paper is to compare and assess the policy initiatives at the unilateral, multilateral, regional and bilateral level and their impact on the host environment which is defined in terms of the key pull factors that have attracted international students to Malaysia. The main findings show that domestic policy initiatives have enhanced the host environment for attracting international students by providing a governance system that protects the interests of international students through its regulations. Efforts to improve quality assurance and accreditation also serve to attract international students. The regulation of fees contributed towards competitively priced programmes that are also pull factors. Multilateral, regional and bilateral commitments are relatively new, emerging only after 2006, and have less potential influence on inflows of international students as these commitments reflect, at best, existing practices in this sector.